Role of Histopathology in diagnosis of Soft Tissue Tumors at Tertiary Care Center - Gautam, Nikita; Makaju, Ramesh; Dhakal, Rachana; Basnet, Dipika; Lama, Binita (Birat Journal of Health Sciences, 2022)
Introduction: Soft tissue tumors (STTs) are a diverse group of neoplasms. It varies from the most common benign tumors to some self-limited lesions and rare malignant soft tissue tumors. Because of the overlap in their clinical and radiological characteristics, histopathology is crucial in determining their diagnosis. Objectives: To study the relative frequencies of types of soft tissue tumors (benign, intermediate and malignant) as well as their histological pattern in relation to age, gender and site of distribution. Methodology: This was a retrospective study conducted over a period of three years from January 2018 to December 2020 in the Department of Pathology, Dhulikhel Hospital, Kavre Nepal. This study included STTs of all the anatomical sites excluding STTs of the female reproductive system. The tumors were classified as benign, intermediate, or malignant using the WHO 2013 classification of soft tissue and bone tumors. The sarcomas were further graded into grades 1, 2, and 3 using the FNCLCC (French Federation Nationale des Centres de Lutte Contre le Cancer) grading system. Immunohistochemistry (IHC) and special staining procedures were also performed as and when required. Result: A total of 198 STTs were studied, of which benign cases were 191 (96.45%), intermediate 03 (1.52%) and malignant 04 (2.03%) in number. The most common type of STTs was vascular tumors 77(38.89%) followed by adipocytic tumors 52(26.26%) and nerve sheath tumors 13(6.56%). STTs were most common in the third decade of life, with the head and neck region being the commonest site. All four malignant tumors were categorized using the FNCLCC grading system. There were three cases of Grade 2 sarcoma and one case of Grade 3 sarcoma. Conclusion: The most common benign tumors were vascular tumors followed by adipocytic tumors and nerve sheath tumors. STTs were most common in the third decade of life. Benign tumors were more common than malignant tumors. In comparison to malignant tumors, benign tumors were found at a younger age group. STTs were found mainly in the head and neck region followed by upper and lower limbs. Despite the fact that molecular diagnostics is gaining popularity in the field of soft tissue tumors, histopathology still remains the gold standard.